Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pt Connect Electrical Engineering Di Kota Batam - Atmojo, Agus Sekti Susila (Tractare: Jurnal Ekonomi-Manajemen, 2022)
The riset is made under the title “The Influence of Work Motivation and Compensation on Employee Performance at PT Connect Electrical Engineering in Batam City.” The purpose of this research is to find out how much the influence of work motivation and compensation on employee performance at PT Connect Electrical Engineering in Batam City. Data collection techniques used in this study in the form of research by distributing questionnaires and literature studies. Research method using quantitative research technique. The number of sample in this research is 66 respondents. The result showed that the regression equation formed was Y =-3,438 + 0,496X1 + 0,767X2. The results of this study indicate that alone, work motivation has a positive and significant effect on employee performance and compensation has a positive and significant effect on employee performance. While together, work motivation and compensation have positive and significant effect on employee performance at PT Connect Electrical Engineering in Batam City. This decision is based on a significance level of F value of 0.000 smaller than a = 0.05.